How do tax compliance labels impact sharing platform consumers? An empirical study on the interplay of trust, moral, and intention to book - David Dann; Raphael Müller; Ann-Catherin Werner; Timm Teubner; Alexander Mädche; Christoph Spengel (Information Systems and e-Business Management, 2022)
The platform economy has generated various new and highly successful business models. However, certain models facilitate tax evasion for service providers on their income earned on these platforms. While tax evasion contradicts the pro-social claim of many sharing platforms, it is unclear whether a provider's tax honesty constitutes a value for consumers at all. This study investigates the role of tax compliance for platform users by employing an online experiment ( n=286). The results indicate that consumers perceive providers' tax compliance and consider it as a trust-enhancing signal. In further analysis, we find that consumers' moral norms moderate both the signal's trust-building effect as well as the relation between trust and transaction intention. In light of recent policy debates around taxing the platform economy, this study provides valuable practical insights for tax legislators.
Keywords: 650; Platforms; Taxation; Compliance; Trust; Moral norms